Psychosocial interventions for building resilience of informal carers of people living with stroke: a systematic review. Issue 9 (24th April 2023) - Qureshi, Ayesha; Hargest, Claire; Swain, Nicola; Aldabe, Daniela; Hale, Leigh
Abstract: Purpose: To identify and synthesise the evidence of interventions purported to build resilience among informal carers of stroke survivors. Methods: A systematic review of randomised controlled trials of psychosocial interventions to build resilience for carers of people post-stroke was planned. A systematic search was conducted in seven online databases from inception to March 2021. Outcomes measured were resilience and its proxy constructs including copying, adaptation, adjustment, problem-solving, self-efficacy, locus of control, competence and strength. Results: Twelve studies were included in the review and were grouped into four intervention categories (i) Education and social support, (ii) problem-solving skills, (iii) problem-solving skills, and psychoeducation and (iv) information provision, problem-solving skills and psychoeducation. Level of evidence A exists for interventions that combine information provision, problem-solving skills and psychoeducation over the interventions that only use problem-solving skills intervention or problem-solving skills with psychoeducation strategies. All interventions apart from one reported significant within and/or between group changes in outcomes. Conclusion: Interventions comprising of information provision, problem-solving skills and psychoeducation appear to be beneficial to improve resilience of carers. However, because of the heterogeneity of the interventions and outcome measures reported across the twelve studies no particular intervention could be definitively supported. Clinical trial registration: Systematic review registration: CRD 42020172824 https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020172824 IMPLICATIONS FOR REHABILITATION: Providing care for stroke survivors is particularly demanding due to the lack of preparation for managing the unexpected and complex nature of stroke, resulting in negative physical, social, behavioral, emotional, and financial outcomes. The long-term nature of stroke and its many residual problems can negatively affect the physical and psychological well-being of the individual and their carers, which may subsequently affect the recovery of the stroke survivor. Evidence suggests that resilience is the protective shield for carers' stress and burnout. Integrating interventions focusing on carers' resilience as part of the stroke rehabilitation process is imperative to ensure the well-being of carers and the sustainability of the care provided to the stroke survivor.